Growth of Potato Mericlone Shoots (Solanum tuberosum L.) At Several Concentrations of Kinetin And Coconut Water - Tambun, Vistria; Lengkong, Edy Fredy; Runtunuwu, Semuel David; Supit, Paula C. H.; Tumewu, Pemmy; Inkiriwang, Annatje E. B.; Sompotan, Saartje; Liwu, Suzanne Laura; Doodoh, Beatrix; Mamarimbing, Rinny (Jurnal Agroekoteknologi Terapan, 2024)
This study aims to determine the effect and concentration of kinetin on potato mericlon shoots and to determine the best effect and concentration of coconut water on potato mericlon shoots. This research was conducted at the Plant Genetics Laboratory, Faculty of Agriculture, Sam Ratulangi University, Manado. This study used a completely randomized design (CRD) which consisted of seven treatments namely A0 (control/no treatment), A1 (Kinetin 0.5 ppm), A2 (Kinetin 1.5 ppm), A3 (Kinetin 1.5 ppm), A4 ( Coconut Water 5%), A5 (Coconut Water 7.5%), A6 (Coconut Water 10%). The variables observed were: shoot height, number of leaves, number of roots, and fresh weight. The results showed that the treatment of kinetin and young coconut water had a significant effect on the parameters of shoot height, namely A6 (6.74 cm), number of leaves, namely A1 (8.2 strands) and A6 (8.2 strands), number of roots, namely A3 (11 .3 units) and a wet weight of A3 (0.4591 gram). In this study, a kinetin concentration of 0.5 ppm was good for increasing the number of leaves, and a concentration of 10% coconut water was good for increasing shoot height. Keywords: Potato, Tissue Culture, PGR, Kinetin, Coconut Water. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh dan konsentrasi kinetin terhadap tunas meriklon kentang dan untuk mengetahui pengaruh dan konsentrasi terbaik air kelapa terhadap tunas meriklon kentangPenelitian ini dilaksanakan di Laboratorium Genetika Tanaman, Fakultas Pertanian, Universitas Sam Ratulangi Manado. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) yang terdiri dari tujuh perlakuan yaitu A0 (kontrol/tanpa perlakuan), A1 (Kinetin 0,5 ppm), A2 (Kinetin 1 ppm), A3 (Kinetin 1,5 ppm), A4 (Air Kelapa 5%), A5 (Air Kelapa 7,5%), A6 (Air Kelapa 10%). Variabel yang diamati adalah: tinggi tunas, jumlah daun, jumlah akar, dan berat basah. Hasil penelitian menunjukan pemberian perlakuan kinetin dan air kelapa muda berpengaruh nyata terhadap parameter tinggi tunas yaitu A6 (6,74 cm), jumlah daun yaitu A1 (8,2 helai) dan A6 (8,2 helai), jumlah akar yaitu A3 (11,3 unit) dan berat basah yaitu A3 (0.4591 gram). Pada penelitian ini, konsentrasi kinetin 0,5 ppm sudah baik untuk peningkatan jumlah daun, dan konsentrasi air kelapa 10% sudah baik untuk meningkatkan tinggi tunas. Kata kunci: Kentang, Kultur Jaringan, ZPT, Kinetin, Air Kelapa